A valuation based theory of learning’s origin and development - Moneymaker, Vincent B. (Frontiers in Systems Neuroscience, 2025)
This paper proposes that learning in animals occurs thru sleep and is fundamentally driven by dynamic information valuation processes. These take the form of either pain and pleasure sensations or the more nuanced emotions that evolved from them. Acting as value identifiers, these sensations and emotions enable animals, from the simplest to the most complex, to mark valuable experiences for both retention and later recall. In this way, the paper argues that learning itself is made possible. The remainder of the paper explores the cognitive, neurological and behavioral implications of this framework, including several novel, testable hypotheses derived from it.